Rate of Solute Incorporation to Liposomes Evaluated from Encapsulated Enzymes Activities - Lissi-Gervaso, E; Calderon-Espinoza, C; Calderon-Espinoza, C; Ahumada-Escandon, M; Ahumada-Escandon, M (2014)
Sin Editorial Disponible